EFFECTS INDUCED BY USING THE SPECIFIC CROSS-COUNTRY SKIING MATERIALS TOWARDS IMPROVING TECHNICAL COMPONENTS IN SKI JUMPING - Wilhelm-Robert GROSZ (Editura Universitatii Transilvania din Brasov, 2018)
The aim of the study is to identify and implement new methods in approaching sports training in ski jumping towards improving technical actions of the athletes in phase I. Practising phase I - the inrun and the takeoff with cross-country has contributed substantially to improving the technical performance of the subjects, which was reflected in the increased length of the jumps. The subjects were four athletes, members of the CSU Brasov jumping ski section, aged 18-20 years. Specific training methods on cross-country skis: adopting the inrun position, alternating the height of the start bar; adopting the inrun position, CM's controlled lifting and lowering during sliding; maintaining a steady inrun position while adopting different upper limbs actions; maintaining a stable position when passing through the transition curves R1 at different angles; adopting and maintaining the inrun position with eyes closed. The study results highlight the positive impact of using this means of sports training on the balance and skill education, on the formation of the sense of proprioception, with a positive motor transfer to the technical performance of the ski jumping execution itself